Evaluation of a pulsed terrestrial laser scanner based on ISO standards. (13th February 2015) - Tsakiri, M; Pagounis, V; Arabatzi, O
Abstract: The evaluation of the accuracy and precision of measuring equipment is critical in order to achieve results that meet the specifications of a given project. Standard calibration models and field procedures exist for all traditional surveying instruments, but are still lacking for recently developed technologies like terrestrial laser scanners (TLS). The main reason is limited knowledge of errors that affect these systems, owing to the proprietary design of the scanners and their software, and the integration of many potential sources of error. Owing to the difficulty of separating the different error sources of TLS, it is proposed in this paper that a test procedure can assess the overall achievable precision for a scanner instrument without individual errors being known. The proposed tests are based on the International Organization for Standardization specifications for geodetic instruments (www.iso.org ). The tests can be performed in either a controlled or uncontrolled environment, which is advantageous for on-the-job calibration. A pulsed terrestrial laser scanner (Leica Scanstation 2) was used as a test subject and the evaluation results indicated that the specific instrument performed well within the manufacturer's specifications.